Graphene promoted oxygen vacancies in perovskite for enhanced thermoelectric properties. (February 2017) - Feng, Xiaopeng; Fan, Yuchi; Nomura, Naoyuki; Kikuchi, Keiko; Wang, Lianjun; Jiang, Wan; Kawasaki, Akira
Abstract: Oxygen vacancy plays an important role in optimizing the thermoelectric properties for achieving high figure of merit in perovskite oxides. However, it remains very challenging to find a facile and effective method for creating oxygen vacancy in bulk perovskite material. Using undoped strontium titanate (STO) as a model for perovskite, it is demonstrated here that incorporating graphene into STO can promote the formation of oxygen vacancy in perovskite far more effectively than the time and energy consuming hydrogen reduction method. With only 0.64 vol% of graphene content, reduced graphene oxide (RGO)/STO composite shows highly increased electrical conductivity and power factor compared to hydrogen reduced STO. Electron energy loss spectrum confirms the high concentration of oxygen vacancy in the area close to RGO in RGO/STO composite, which suggests a mild reaction between RGO and STO during sintering. In addition, the thermal conductivity is also depressed due to greatly restricted grain growth via adding RGO. Therefore, this study provides a fast, green and effective way of preparing oxygen deficient perovskite towards improved thermoelectric properties. Graphical abstract: